Experimental investigation of mechanical dicing parameters on the quality of thin glass wafer cutting process - Liou, Jacqueline Jing Wen (2020)
Silicon-glass device has been adopted in the industry especially used on applications like pressure sensor, accelerometer, microfluidic device, micropump, microturbine, and micro-actuator. In this study, the focus of the package application is current sensors with component of an ultra-thin silicon device bonded on top of a thin glass chip. Other than that, both of the chip is mounted on DAF tape for a cheaper assembly solution. There are no experience in Infineon to process glass wafer mounted on DAF dicing tape which is a key challenges in this project. Hence, the purpose of this study was to create a solution in die separation of glass wafer. Therefore, it is crucial that process characterisation of glass wafer dicing by using mechanical dicing method. This project is defined to comply with automotive specifications especially on dicing induced quality risk such as top side chipping, side wall chipping, back side chipping and other defects. Research and philosophy on glass wafer dicing method is harvested and referred as past experience learning. Design of experiments is developed based on the critical parameters in mechanical dicing. Then, the result will based on design model method by using Minitab software. With the help of response surface methodology, optimized parameters has been selected. The outcome of this project is glass wafer dicing are able to finalized by using mechanical dicing method with the optmized parameters. Out of 11 DOEs, DOE 7 has been selected as the best solution and repeatability run has shown positive results. However, blade life study is recommended to perform as the blade used are new resin blade.